Empathy, Theory of Mind, and Prosocial Behaviors in Autistic Children - Wang, Xin; Auyeung, Bonnie; Pan, Ning; Lin, Li-Zi; Chen, Qian; Chen, Jia-Jie; Liu, Si-Yu; Dai, Mei-Xia; Gong, Jian-Hua; Li, Xiu-Hong; Jing, Jin (Frontiers in Psychiatry, 2022)
Background: Previous research has suggested that children with autism spectrum disorder (ASD) display fewer prosocial behaviors, and the role of empathy or Theory of Mind (ToM) in prosocial behaviors of autistic children remains unclear. Method: Data were obtained from an ongoing longitudinal study in Guangzhou, China. A total of 96 autistic children and 167 typically developing (TD) children were enrolled. Prosocial behaviors were assessed using a subscale of the Strength and Difficulties Questionnaire and Dictator Game (DG) paradigm with stickers as incentives. Empathic traits and ToM ability were measured using the children’s Empathy Quotient and the Chinese version of ToM toolkit. Generalized linear models were used to assess the differences of prosocial behaviors and empathic traits, ToM ability between the two groups and the associations between empathic traits, ToM ability and prosocial behaviors in autistic children. Result: Compared with TD children, autistic children exhibited worse ToM ability and performed less pro-socially in the DG paradigm, while there were no differences regarding empathic traits. In autistic children, empathic traits especially affective empathy, were positively associated with parent-reported prosocial behaviors (β=0.17, 95% confidence interval [CI]: 0.07-0.27; β=0.47, 95%CI: 0.33-0.60). ToM ability was associated with DG paradigm (β =1.03, 95%CI: 0.16,1.89). Conclusion: Autistic children showed less pro-sociality and ToM ability than TD children. In autistic children, empathic trait was associated with parent-reported prosocial behaviors while their ToM ability was associated with prosocial behaviors in experimental condition. Our findings indicated that better ToM ability and empathic trait might promote prosocial behaviors in autistic children.